Cardiac rehabilitation meta-analysis of trials in patients with coronary heart disease using individual participant data (CaReMATCH): Project protocol. (December 2020) - Buckley, Benjamin J.R.; Kleinnibbelink, Geert; Lip, Gregory Y.H.; Taylor, Rod S.; Thijssen, Dick H.J.
Abstract: Background: Exercise-based cardiac rehabilitation (CR) has long been a cornerstone in the secondary prevention of coronary heart disease (CHD). Despite meta-analyses of randomised trials demonstrating a positive impact of CR on cardiovascular mortality, hospitalisation, exercise capacity and health related quality of life, the impact of CR on all-cause mortality remains uncertain, especially in the context of contemporary clinical practice. This CR meta-analysis of trials in patients with coronary heart disease using individual participant data (IPD) (CaReMATCH) seeks to (1) provide definitive estimates of the effectiveness of CR in terms of all-cause mortality, cardiovascular mortality, hospitalisation and health-related quality of life, and (2) determine the influence of individual patient characteristics (e.g. age, sex, risk factors) on the effectiveness of CR to inform a personalised CR-approach. Methods: Randomised controlled trials will be identified that were performed in the last decade, to ensure that CR was performed in combination with contemporary medical care (2010–2020). For our first aim, outcomes of interest include all cause- and CVD-related mortality and hospitalisations. To answer our second research question, we will collect data on exercise capacity, health-related quality of life, and patient baseline demographic and clinical data. Original IPD will be requested from the authors of all eligible trials; we will check original data and compile a master dataset. IPD meta-analyses will be conducted using a one-step meta-analysis approach where the IPD from all studies are modelled simultaneously whilst accounting for the clustering of participants within studies. Discussion: Findings from CaReMATCH will inform future (inter)national clinical and policy decision-making on the (personalised) application of exercise-based CR for patients with CHD.